Offshoring and the New Age Employee: Emerging Issues in Human Resource Management (Journal of Organizational Psychology, 2020)
As organizations continue to “offshore” their operations across national boundaries, they also reconfigure their relationship with their workforce. In this paper, we examine the impact of offshoring on the employer-employee contract, primarily through the lens of the exit-voice argument proposed by the economist Alfred Hirschman in 1970. Our contention is that offshoring reconfigures the employer-employee relationship, replacing earlier psychological contracts with an increasingly transactional character. We present a framework of new HR imperatives that confront organizations and employees in the post-offshoring age, and discuss the ethical challenges facing organizational theorists, who represent this debate in their research and the classroom.
Keywords: Organizational Psychology; Offshoring; Human Resource Management